Degradation of Binocular Coordination during Sleep Deprivation - Tong, Jianliang; Maruta, Jun; Heaton, Kristin J.; Maule, Alexis L.; Rajashekar, Umesh; Spielman, Lisa A.; Ghajar, Jamshid (Frontiers in Neurology, 2016)
To aid a clear and unified visual perception while tracking a moving target, both eyes must be coordinated so the image of the target falls on approximately corresponding areas of the fovea of each eye. The movements of the two eyes are decoupled during sleep, suggesting a role of arousal in regulating binocular coordination. While the absence of visual input during sleep may also contribute to binocular decoupling, sleepiness is a state of reduced arousal that still allows for visual input, providing a context within which the role of arousal in binocular coordination can be studied. We examined the effects of sleep deprivation on binocular coordination using a test paradigm that we previously showed to be sensitive to sleep deprivation. We quantified binocular coordination with the standard deviation of the distance between left and right gaze positions on the screen. We also quantified the stability of conjugate gaze on the target, i.e. gaze-target synchronization, with the standard deviation of the distance between the binocular average gaze and the target. Sleep deprivation degraded the stability of both binocular coordination and gaze-target synchronization, but between these two forms of gaze control the horizontal and vertical components were affected differently, suggesting that disconjugate and conjugate eye movements are under different regulation of attentional arousal. The prominent association found between sleep deprivation and degradation of binocular coordination in the horizontal direction may be used for a fit-for-duty assessment.